Pengaruh Firm Size, Audit Fee, Audit Tenure, Kompetensi dan Independensi Auditor Terhadap Kualitas Audit pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia 2018-2022 - Finnie, Finnie; Simorangkir, Enda Noviyanti; Lavita, Cynthia; Tanadi, Wilsen; Siregar, Fhikry Ahmad Halomoan (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of firm size, audit fees, audit tenure, auditor competency and independence on audit quality in banking companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This research population used a purposive sampling technique to obtain a sample of 150 data from 30 companies, but data transformation and outliers were applied so that the sample size became 120 data. The data analysis applied in this research is classical assumption testing, multiple linear regression analysis, and hypothesis testing. The research results show that simultaneously there is an influence of the variables firm size, audit fee, audit tenure, competence and independence of the auditor on audit quality, but partially the variables of competence and independence of the auditor do not have a significant effect on the quality of audits in banking companies listed on the Indonesia Stock Exchange for the period 2018-2022.